Lectotypification of Actinodaphne lanata Meisn. (Lauraceae) and notes on its occurrence in the Western chats, India - Robi, A. J.; Anilkumar, K. A.; Udayan, P. S. (Bangladesh Journal of Plant Taxonomy, 2017)
Not available. Keywords: Actinodaphne; Critically Endangered; Lauraceae; Lectotype; Southern Western Ghats. Bangladesh J. Plant Taxon. 24(1): 119123, 2017 (June)